Los peces del arrecife de Cabo Pulmo, Golfo de California, México: Lista sistemática y aspectos de abundancia y biogeografía - Villarreal-Cavazos, Antonio (Universidad de Costa Rica, 2000)
The Cabo Pulmo reef is the most important coral formation of the Gulf of California; however, its ichthyological fauna has been poorly studied. To produce a systematic list with data on relative abundance and frequency, and biogeographical affinities, we relied on visual census, field observatíons, analysis of commercial and sport fisheries (from 1986 to 1998), and the literature. A total of 236 species have been recorded at Cabo Pulmo (155 genera and 60 families). This number doubles previous compilations and represents 65.1 % of aH reef fishes known from the Gulf of California, and about 35% of its entire shallow-water fishes. Of the total species number, 68.3% are from the Panamic Province, 11.0% Indo Pacific colonizers and the same percentage gulf endemics, 7.6% are circumtropical, 1.7% Atlantic and 0.5% cosmopolitan; none are endemic to the reef. The most abundant taxa are the Jabrids Thalassoma lucasanum, T grammaticum and the pomacentrid Chromis atrilobata. Only eleven species (4.7% of total) appeared in 75% to 100% of census, and 36 (15.3% oí" total) had high levels of both abundance and frequency, evidencing that the communíty is dominated by few taxa. Local species richness exceeds the number reported for most rocky or coral reefs of the Pacific coast of México. and indicates that Cabo Pulmo is a key area in the gulf and the entire Mexican Pacific, from the ichthyolC1gical point of view.